The career progression of masters in business administration (MBA) graduates: the case of university of Limpopo graduates between 2007 and 2011 - Sekole, Mohlatlego Glostine (University of Limpopo, 2015)
The contribution of an MBA degree on career mobility in South Africa is of importance and exhibits strong interest from academics, business and public space. Many people believe that an MBA can help for any managerial position especially in cooperate business set up in terms of upward career mobility and skills acquisition. This study wanted to find out if indeed qualifying with an MBA degree helps graduates to move upward, get better salaries and benefits and feel more skilled.This study was conducted using graduates from the Turfloop Graduate School of Leadership, University of Limpopo, who graduated between 2007 and 2011. A total of 44 participants responded. The results mainly indicated that the MBA qualification does help in helping graduates feel better capacitated and ready for managerial positions. The qualification also helps with higher positions and/or salaries. However, for candidates to realise those better positions they mostly need to move to other organisations or even other provinces.The study recommends that another study focused on more universities that offer MBA in South Africa be carried out to compare the career advancement of graduates from all these universities. Another one that focuses on the reasons why career progression is not mostly realised in organisations within which candidates worked prior to getting an MBA degree is also recommended.
Thesis (MBA.) -- University of Limpopo, 2015
Keywords: Career development; Business; Career development; Business management